Dispersion of oxides, heavy metals, and natural radionuclides in phosphogypsum stockpiles of the phosphate industries in Türkiye - Turhan, Şeref; Altuner, Ergin Murat; Ayata, Aytaç; Gezer, Ferhat; Hançerlioğulları, Aybaba; Kurnaz, Aslı; Karataşlı, Muhammet (Springer Science and Business Media LLC, 2025)
Abstract Heavy metal (HM) and naturally occurring radioactive materials (NORM) pollution is continuously increasing due to anthropogenic activities, and it is one of the global problems that pose a threat to human and environmental health. Phosphogypsum (PG), a by-product of phosphate fertilizer (PF) production, is an industrial solid waste produced in large quantities worldwide, and much of it is stockpiled. PG contains enhanced levels of toxic substances such as HMs and NORMs. The first detailed study on the determination of major-minor oxides, HMs, and NORMs contents of PGs collected from waste stockpiles at phosphate fertilizer factories (PFFs) in Türkiye was carried out using energy-dispersive X-ray fluorescence spectrometry to obtain data for the reuse of these wastes and a better characterization of the waste deposit. The major-minor oxides analyzed in the PG samples were ranked as SO3 (53.22%) > CaO (36.84%) > SiO2 (2.08%) > P2O5 (1.21%) > Al2O3 (0.13%) > Fe2O3 (0.11%) according to their average contents. The average contents (mg/kg) of HMs and NORMs analyzed in the PG samples were listed as follows: Fe (744.2) > Ti (102.1) > Zn (59.2) > Mn (28.9) > Ni (18.4) > Cr (15.2) > Co (14.6) > Cu (13.5) > Zr (10.8) > Pb (8.8) > Cd (8.5) > V (7.4) > U (4.9) > Th (4.2). The results revealed that HMs, except Cd and U, were lower than the Earth’s crust averages and maximum soil contaminant levels recommended in the Turkish Regulation on Control of Soil Pollution.
Keywords: Radioisotopes; Turkey; Metals, Heavy; Phosphorus; Oxides; Fertilizers; Calcium Sulfate; Research Article; Phosphates